Neotropical Hemerodromia Meigen (Diptera: Empididae), a world of discovery II: New species from Atlantic forest, Brazil - Câmara, Josenir T.; Takiya, Daniela M.; Plant, Adrian R.; Rafael, José A. (Zootaxa, 2015)
Eight new species of Hemerodromia Meigen are described from the Brazilian Atlantic forest, H. brevicercata sp. nov., H. carioca sp. nov., H. cornuhypandrialis sp. nov., H. megalamellata sp. nov., H. membranosa sp. nov., H. mourai sp. nov., H. cummingi sp. nov., and H. ubajaraensis sp. nov. are described and illustrated. This is the first record of the genus from the Brazilian southeast and northeast.